University of Portsmouth library subject pages: a flexible in-house system for guidance and resource discovery - Collinson, Timothy; Porter, Hannah; Work, Colin K. (The Journal of academic librarianship, 2022)
Guiding students to library resources, and supporting users in their discovery and use, is a key role of academic librarians. Subject pages are a traditional way of asynchronously managing some of the complexity that exists, with off-the-shelf software packages often a solution. The University of Portsmouth Library (https://library.port.ac.uk/) decided to provide this support through an addition to our existing in-house content management system (CMS). This would be flexible and powerful in allowing freedom of design for Faculty Librarians within a shell that provided some similarity – and thus familiarity – between subject areas. It would also be easy to maintain technically. The Library's Web Developer, in consultation with the six Faculty Librarians and the Enquiry team lead, has built a PHP/MySQL based application which is tightly integrated to our existing web resources providing enhanced delivery mechanisms allowing for open ended content development while retaining support for legacy web pages. This allows new pages to be quickly and easily added to the system in real time, existing pages to be either edited alone, ‘linked to’ or copied and modified. Resource lists can be simply constructed which rely on Library metadata rather than copies of data which need updating; support material can be added whether video, slides or images; guidance can be included to help students navigate their information literacy journey. Despite a pressured summer period of lockdown and working from home due to Covid-19, the rollout of the system has been successful from the point of view of the faculty librarian construction and development, as well as in usage by our enquiries team supporting students requiring help. Student feedback has been positive.